Turkic "Hikaya" genre and its characters - Akhmetbekova, Akbota; Auyesbayeva, Pakizat; Ibrayev, Shakimashrip (Opción, 2018)
One of the complex genres in narration, legend prose of Turkic language people is called “hikaya”.Why do we distinguish this genre? What are the criteria for determining this genre? How does it differ from other genres of Turkic folklore? How to differentiate its characters? Why is the genre of "hikaya" still taking place in the worldview of modern people? It is these issues that enable us to single out the genre of "hikaya" in Turkic literature. Hikaya (true story) is based on the belief in the existence of various evil beings, a meeting with which brings a person misfortune and trouble.